2011
DOI: 10.1002/ca.21134
|View full text |Cite
|
Sign up to set email alerts
|

An anatomic study using three‐dimensional reconstruction for pterygopalatine fossa infiltration via the greater palatine canal

Abstract: The pterygopalatine fossa (PPF) is accessed via the greater palatine canal (GPC) in an attempt to reduce bleeding during paranasal sinus surgery. This study aims to investigate the anatomy of the greater palatine foramen (GPF), GPC, and the PPF, with reference to PPF infiltration using three-dimensional reconstruction of computer tomographic (CT) scan measurements. The CT scans of 50 patients were retrospectively evaluated. The morphology of the GPF, GPC, and the PPF was assessed in a three-dimensional model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 12 publications
1
31
0
2
Order By: Relevance
“…For example, the GPA at the position of the GPF could be damaged by a misdirected osteotome during maxillary osteotomy, as well as during excessive harvesting of graft tissue in periodontal plastic surgeries. Many studies have investigated the location and diameter of the GPF (Kim et al, ; Methathrathip et al, ; Hwang et al, ). The location of the GPF varies with race (Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the GPA at the position of the GPF could be damaged by a misdirected osteotome during maxillary osteotomy, as well as during excessive harvesting of graft tissue in periodontal plastic surgeries. Many studies have investigated the location and diameter of the GPF (Kim et al, ; Methathrathip et al, ; Hwang et al, ). The location of the GPF varies with race (Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It descends in the pterygopalatine canal and travels through the greater palatine foramen (GPF) together with the greater palatine nerve. The GPF is located just anterior to the posterior edge of the hard palate, and can be found by palpating the palate with the finger (Hwang et al, ). After passing the GPF, the name of the artery changes to the greater palatine artery (GPA), and it supplies posterior two‐thirds of the hard palate as it runs anteriorly in a curved groove near the alveolar ridge (Klosek and Rungruang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hwang et al in 2011 [7] studied 55 CT scans and found that the transverse diameter of the GPF in male is significantly larger than that of the female. Patil et al [8] in 2016 studied 123 dry skulls in which both the transverse diameter and AP diameters were significantly largerin males.…”
Section: Discussionmentioning
confidence: 99%
“…Methathrathip et al (4), and Urbano et al (5) evaluate it on dry skulls, while others used the imaging technology like CT, CBCT, etc. (1, 6-10). …”
Section: Discussionmentioning
confidence: 99%
“…Concerning the canal length, it was either assessed as an isolated entity from the PPF (6, 10), or considered extending superiorly from different landmarks in the PPF such as the higher bony aspect of the PPF (11), the foramen rotundum (4), the sphenopalatine foramen (9), and the vidian canal (1, 7, 8) to the greater palatine foramen inferiorly.…”
Section: Discussionmentioning
confidence: 99%